2021
DOI: 10.1155/2021/8835677
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice towards Labor Pain Management and Associated Factors among Skilled Birth Attendants Working at Hospitals Found in Central, West, and North Gondar Zones, Northwest Ethiopia, 2019: A Multicenter Cross-Sectional Study

Abstract: Introduction. Delivery of the infant into the arms of a conscious and pain-free mother is the most exciting and rewarding moment in maternal care services. Physical and mental care of women during delivery requires good knowledge and a positive insight to the needs and rights of the mothers. Little was known regarding skilled birth attendants’ knowledge, attitude, and practice towards labor pain management in the study area. Hence, the current study aimed at assessing knowledge, attitude, and practice, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…In this study, three hundred five 65.5% [(95% CI (60.9, 69.8)] of the study participants have unfavorable attitudes. This is higher than studies done in Benishangul Gumuz Regional State 53% [ 22 ] and Gondar Ethiopia 58.04% [ 20 ]. This discrepancy may be due to socio-cultural differences among study participants and a higher sample size of the current study than studies done in Gondar [ 20 ] and Benishangul Gumuz Regional State [ 22 ].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In this study, three hundred five 65.5% [(95% CI (60.9, 69.8)] of the study participants have unfavorable attitudes. This is higher than studies done in Benishangul Gumuz Regional State 53% [ 22 ] and Gondar Ethiopia 58.04% [ 20 ]. This discrepancy may be due to socio-cultural differences among study participants and a higher sample size of the current study than studies done in Gondar [ 20 ] and Benishangul Gumuz Regional State [ 22 ].…”
Section: Discussioncontrasting
confidence: 57%
“…This is higher than studies done in Benishangul Gumuz Regional State 53% [ 22 ] and Gondar Ethiopia 58.04% [ 20 ]. This discrepancy may be due to socio-cultural differences among study participants and a higher sample size of the current study than studies done in Gondar [ 20 ] and Benishangul Gumuz Regional State [ 22 ]. This implied that concerned bodies should work together to improve the attitude of obstetrics care providers through different strategies such as facilitating continuous educational opportunities which have a profound effect on addressing the women’s need of alleviating labor pain.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…One's own personal birth experience can also be positively correlated with attitudes about and intent to provide PLS [19], along with age and length of experience [1,12]. Furthermore, good knowledge in relation to pain relief in labor and working at private primary hospitals have also been found to be statistically significant in relation to favorable attitudes and clinical practice [20,21]. Other factors associated with the low levels of supportive behavior provided by midwives for women in labor relate to their workload and shift length [14,18].…”
Section: Introductionmentioning
confidence: 95%
“…This may be due to adequate space, staff, and equipment. It comes along with a study done by [21] in Ethiopia on 336 skilled attendants who, revealed that more than half of the study participants had good practice. This is similar to a crosssectional study carried out by [22] in Ethiopia among 464 healthcare professionals.…”
mentioning
confidence: 97%